Psychological Anomie (Srole’ s Scale) and the Unemployed in Croatian Society - Vukelić, Anton (Array, 2007)
Based on the pool on about 400 unemployed persons, statistical connection between Srole's scale of anomie as a particular indicator of disappointment and two objective and two subjective characteristics of unemployed is being questioned. Results indicate that probability of employment is not connected with psychological anomie. Almost identical result is applicable for the age variable. On the other hand, unemployed persons who show low score on externality scale or are under strain about getting employed express more disappointment with society and their position in it.